Finnish general upper secondary students' metacognitive awareness in foreign language learning. Issue 4 (4th July 2021) - Mäkipää, Toni; Kallio, Manne; Hotulainen, Risto
ABSTRACT: Our objective with this study was to investigate students' metacognitive awareness (MA) and its association with course grades in general upper secondary foreign languages, to foster reflective practices. A total of 267 foreign language students at Finnish schools answered an online survey, and the data were analysed quantitatively. Based on the results, the students' levels of MA were high in foreign languages, students at urban schools had higher levels than students at rural schools, and students with high course grades had higher levels of MA. Knowledge of cognition and attitudes about the language predicted the course grade the most. The results indicate that more emphasis should be put on the enhancement of MA at rural schools and with low-achieving students, to enhance their reflective practices.